Design And Development of a Compact Carbon Gas Emission Monitoring Device for Private Vehicles - Teodoro Christine Ann; Facunla Rowel; Milan Ferdinand; Deo John Robert; Vinoya Christine Marie (E3S Web of Conferences, 2024)
Poor air quality is a major concern in urban areas, with a large percentage of the population exposed to high levels of pollutants. Using sensor and monitoring technology, devices can automatically and periodically monitor indoor air quality. Containment measures should be taken when dangerous airborne chemicals are detected. Air pollution, both indoors and outdoors, causes health problems. The Philippines faces challenges in air quality reporting due to the high cost of monitoring equipment. A project is underway to collect real-time data using sensors and an Arduino Uno-based monitoring system. The power management design's PCB layouts were completed using two software applications: Eagle CAD for the nano power boost charger circuit and Ultiboard for the boost converter circuit. The layout design adhered to the IPC2221A standards, ensuring accurate component footprints and copper trace width, which were determined based on the current flow through the trace in the PCB design. The circuit boards were carefully sized to be smaller than 4“x4” to enable smooth integration into an air quality monitoring device. The integrated design functioned as a wireless sensing application, effectively monitoring air quality. The carbon gas monitoring system had the capability to detect and collect various gases, including Carbon Dioxide, Nitrogen Monoxide, Carbon Monoxide, and Dust Density. Additionally, it was equipped to measure temperature and humidity. Achieving this required using the Arduino Uno application for programming and incorporating an additional sensor, resulting in a cost-effective design solution. The prototype successfully integrated air quality sensors, microcontrollers, and communication modules. The system's performance was evaluated against existing testing centers, and the results were presented.